Evolutions of CO2 Adsorption and Nanopore Development Characteristics during Coal Structure Deformation - Linlin Wang; Zhengjiang Long (Applied Sciences, 2020)
The coal structure deformation attributed to actions of tectonic stresses can change characteristics of nanopore structure of coals, affecting their CO2 adsorption. Three tectonically deformed coals and one undeformed coal were chosen as the research objects. The isotherm adsorption experiments of four coal specimens were carried out at the temperature of 35 °C and the pressure of 0 to 7 MPa. Nanopore structures were characterized using the liquid nitrogen adsorption method. The results show that there exist maximum values of excess and absolute adsorption capacity, which increase with increasing coal deformation degree. As the degree of coal deformation increases, the pore volume and specific surface area present an obvious increasing trend in the case of micropores, exhibiting an increase at first (cataclastic coal and ganulitic coal) and then stabilization (crumple coal), in the case of mesopores, and showing a gradual decrease in the case of macropores. The mesopores are the key factor of CO2 adsorption of tectonically deformed coals, followed by the micropores and the limited effect of macropores at the strong coal deformation stage.